Comparison of blood leptin and vitamin E and blood and adipose fatty acid compositions in wild and captive populations of critically endangered Vancouver Island marmots (Marmota vancouverensis). Issue 2 (29th September 2022) - Aymen, Jessica; Delnatte, Pauline; Beaufrère, Hugues; Chalil, Dan; Steckel, Klaudia. E.; Gourlie, Sarra; Stark, Ken D.; McAdie, Malcolm
Abstract: Vancouver Island marmots ( Marmota vancouverensis ) (VIMs) are a critically endangered species of fat‐storing hibernators, endemic to Vancouver Island, British Columbia, Canada. In addition to in‐situ conservation efforts, a captive breeding program has been ongoing since 1997. The captive diet is mostly pellet‐based and rich in n −6 polyunsaturated fatty acids (PUFAs). In captivity, overall length of hibernation is shortened, and marmots have higher adipose tissue reserves compared to their wild‐born counterparts, which may be a risk factor for cardiovascular disease, the leading cause of mortality in captive marmots. To investigate differences in lipid metabolism between wild and captive populations of VIMs, blood vitamin E, fatty acid (FA) profiles and leptin, and white adipose tissue (WAT) FA profiles were compared during the active season (May to September 2019). Gas chromatography, high‐performance liquid chromatography, and multiplex kits were used to obtain FA profiles, α‐tocopherol, and leptin values, respectively. In both plasma and WAT, the concentration of the sum of all FA in the total lipids was significantly increased in captive VIMs. The n −6/ n −3 ratio, saturated FAs, and n −6 PUFAS were higher in captive marmots, whereas n −3 PUFAs and the HUFA score were higher in wild marmots. Serum concentrations of α‐tocopherol were greater by an average of 45% in captive marmots, whereas leptin concentrations did not differ. Results from this study may be applied to improve the diet and implement weight management to possibly enhance the quality of hibernation and decrease the risk of cardiovascular and metabolic diseases of captive VIMs. Abstract : In the plasma and adipose tissue of captive Vancouver Island marmots ( Marmota vancouverensis ), the concentration of the sum of all fatty acids in the total lipids was significantly higher. The n −6/ n −3 polyunsaturated fatty acid (PUFA) ratio and saturated fatty acids were higher in captive marmots, whereas wild marmots had greater concentrations of n −3 PUFAs.